Impact of elateriospermum tapos supplementation on leptin and hypothalamic signaling in female offspring of high-fat diet-induced obese - Balan, Santhra Segaran; Bahari, Hasnah; Zainal Abidin, Azrina; Shafie, Nurul Husna; Abdullah, Maizaton Atmadini; Jasni, Azmiza Syawani (Tabriz University of Medical Sciences, 2025)
Purpose: The central nervous system plays a crucial role in regulating food intake and energy expenditure to maintain energy homeostasis in the body. With rising obesity rates, alternative therapeutic strategies, including herbal-based interventions, are gaining attention. Elateriospermum tapos a plant that rich in flavonoids, has shown potential supporting weight reduction. This study aimed to evaluate the effects of E. tapos seed and shell supplementation on the hypothalamic feeding pathway in obese female rats and their offspring. Methods: Thirty adult female Sprague-Dawley rats were used in this study. Obesity was induced in 24 rats via high-fat diet (HFD) for five weeks. Six rats were maintained on a normal diet as the control group (DCG). The obese rats were then divided into four groups: negative control (DNG, HFD only), positive control (DPG, HFD + orlistat 200 mg/kg), treatment 1 (DTX1, HFD + E. tapos seed 200 mg/kg), and treatment 2 (DTX2, HFD + E. tapos shell 200 mg/kg). Treatments were administered daily for six weeks before mating. On postnatal day 21 (PND21), blood and hypothalamus samples were collected from female rats and their female offspring. Plasma leptin levels were measured using ELISA, and expression of leptin receptor (Obr), proopiomelanocortin (POMC), and neuropeptide Y (NPY) in the hypothalamus was assessed by western blotting. Results: DTX2 and offspring (OTX2) groups showed significantly (P< 0.05) lower levels of leptin. Western blot results indicate Obr, POMC and NPY protein significantly (P< 0.05) higher expression in DNG and ONG compared to the other groups. Conclusion: In conclusion, the E. tapos shell significantly reduced maternal obesity in female offspring at PND21 compared to its seed.